OSGOOD SCHLATTER DISEASE A RARE CONDITION IN YOUNG ATHLETES A CASE STUDY (International Journal of Physiotherapy, 2014)
Background: Osgood Schlatter disease (OSD) now classified as an apophysitis of the anterior aspect of the tibial tuberosity (ATT) is a common condition in an active youth athletes and is associated with growth spurts. The symptoms of Osgood Schlatter Disease mimics different condition and thus it has to be diagnosed rationally. Clinical features include mild to severe and intermittent or continuous pain, tenderness, swelling and limp while walking. Radiological features include enlarged and fragmented tibial tubercle. Treatment of Protection, Rest, Ice, Compression and Elevation (PRICE) protocol is generally given in the initial stages followed by the complete rehabilitation of athlete into sports.Methods: I present the case of a patient, fifteen year old boy presenting the symptoms of pain, tenderness, swelling and limp while walking. He was referred by Orthopedician and he was on diclofenac medications. His detailed evaluation was carried out and was diagnosed on the basis of history, clinical findings and radiographic investigations as Osgood Schlatter Disease.Treatment: A three phase rehabilitation treatment plan was developed which was typically aimed at return of athlete as early as he can to the sports circuit. In Acute phase, Ice and rest was given; In Recovery phase, strengthening of surrounding musculature was given; In Maintenance phase, changes were made to athlete’s playing style with the help of Coach.Conclusion: Initial assessment, PRICE Protocol and making changes in playing style of the athlete helps in treating Osgood Schlatter Disease. The causative factor has to be looked upon while treating this condition.